Accuracy of an Immunochromatographic Diagnostic Test (ICT Malaria Combo Cassette Test) Compared to Microscopy among under Five-Year-Old Children when Diagnosing Malaria in Equatorial Guinea. (6th July 2010) - Portero, José-Luis; Rubio-Yuste, Maria; Descalzo, Miguel Angel; Raso, Jose; Lwanga, Magdalena; Obono, Jaquelina; Nseng, Gloria; Benito, Agustin; Cano, Jorge
Abstract : Conventional malaria diagnosis based on microscopy raises serious difficulties in weak health systems. Cost-effective and sensitive rapid diagnostic tests have been recently proposed as alternatives to microscopy. In Equatorial Guinea, a study was conducted to assess the reliability of a rapid diagnostic test compared to microscopy. The study was designed in accordance with the directives of the Standards for Reporting Diagnostic Accuracy Initiative (STARD). Peripheral thick and thin films for the microscopy diagnosis and a rapid immunochromatographic test (ICT Malaria Combo Cassette Test) were performed on under five-year-old children with malaria suspicion. The ICT test detected Plasmodium spp. infection with a sensitivity of 81.5% and a specificity of 81.9% while P. falciparum diagnosis occurred with a sensitivity of 69.7% and a specificity of 73.7%. The sensitivity of the ICT test increased with higher parasitemias. The general results showed little concordance between the ICT test and microscopy (kappa = 0.28, se: 0.04). In Equatorial Guinea, the ICT Malaria Combo Cassette Test has proven to be an acceptable test to detect high P. falciparum parasitemias. However, the decrease of sensitivity at medium and low parasitemias hampers that ICT can replace properly performed microscopy at present in the diagnosis of malaria in children.